Pediatric Rhabdomyosarcoma - Shern, Jack F. (Crit Rev Oncog, 2015)
Rhabdomyosarcoma is the most common soft-tissue sarcoma of childhood, and despite clinical advances, subsets of these patients continue to suffer high levels of morbidity and mortality associated with their disease. Recent genetic and molecular characterization of these tumors using sophisticated genomics techniques, including next-generation sequencing experiments, has revealed multiple areas that can be exploited for new molecularly targeted therapies for this disease.